Upaya Meningkatkan Keterampilan 4C Siswa Kelas VIII dengan Strategi Gallery Walk dalam Pembelajaran Matematika di SMP Negeri 3 Tepus - Dwi Hastuti Listiyani (Universitas Islam Ahmad Dahlan (UIAD) Sinjai, 2021)
This research aims to improve VIII grade students’ Creativity, Critical Thinking, Collaboration and Communication skills (4C skills) in SMP N 3 Tepus using gallery walk in mathematics learning. This is a classroom action research. The subject of this research is 21 students of eight grade inSMP N 3 Tepus. The skills measured in this study include: 1) creativity, 2) critical thinking, 3) collaboration, and 4) communication. The data of this study were obtained through observation and students cycle test. The results showed that: (1)implementation of learning with gallery walk strategy contained: (a) choosing text, (b) organize text in the classroom, (c)instruct students how to perform along the gallery, can improve 4C skills of students. (2) The improvement of 4C students skills based on observation and students cycle test in cycle 1 was 58,45 and increased to 75,43 in the end of cycle 2